Penerapan Pencatatan Keuangan Sederhana Berbasis Digital pada UMKM ‘Sulton Bakery’ - Lestari, Intan Fatinah; Rahma Febriyanti; Alda Rahmawati; Kirani, Anbiya Rizky; Johar, Fikrul Haykal; Ade Nugraha; Ahmad, Alief Padlillah; Jamil, Muhamad Wildan; Ramdhani, Muhammad Rizky; Muhammad Rizal; Rastari; Jannah, Siti Zahra Ma’watul; Farhan (LPPM UNINUS, 2023)
The service program is carried out with the aim of providing MSME players with increased knowledge so that they can prepare digital bookkeeping and can prepare Profit and Loss Reports in accordance with applicable guidelines. The data collection method used in this community service program is a qualitative method that uses primary data. The data collection technique used is observation in the form of direct observation and interviews. This digital-based financial bookkeeping training was carried out using Microsoft Excel software. The implementation stages of this program consist of socialization, training and evaluation. As a result, this work program was successfully carried out because MSMEs were able to fill in the General Ledger independently every day and were able to prepare a Profit and Loss Report